A Practical Synthesis of a Potent and Selective Diacylglycerol Acyltransferase-1 (DGAT-1) Inhibitor - Shin, Youngsook; Bergeron, Philippe; Fox, Brian M.; Kayser, Frank; McGee, Lawrence R.; McKendry, Sharon; McMinn, Dustin L.; Labelle, Marc; Cushing, Timothy D. (Synthesis, 2014)
A practical synthesis of a potent, selective, and orally efficacious diacylglycerol acyltransferase-1 (DGAT-1) inhibitor, is described. This synthesis is suitable for multi-kilogram scale with high regioselectivity and stereoselectivity. The synthesis involves a Knoevenagel condensation with Meldrum’s acid followed by the stereoselective addition of phenyl cuprate, regioselective Friedel–Crafts acylation, cyclization, and a regioselective reduction through an enol triflate with catalytic platinum oxide to provide the desired compound in 5.2% yield over 12 steps.
Keywords: diacylglycerol acyltransferase-1; hydrogenation; Knoevenagel condensation; Friedel–Crafts acylation; Friedel–Crafts alkylation; stereoselectivity; regioselectivitiy